Manual Material Handling Analysisi Of Workers Lifting Goods Using The Rappid Upper Limb Assessment (Rula) Method At Pt Intipratama Global Service - Ramdan, Muhamad; Zulfikar, Iwan; Sahrijuita, Sahrijuita (Journal of Industrial System Engineering and Management, 2024)
Manual Material Handling (MMH) Workshop in Maintenance is an activity that humans carry out every day. In this research, the qualitative method is used, which is a research method based on the philosophy of postpositivism, used for research on the natural conditions of objects. Based on the results of research on the level of work posture risk among goods lifting workers at PT Intipratama Global Services when carrying out goods lifting activities, there were 5 informants who displayed the risk level of work posture ranging from medium, high, and very high risk levels. Based on the results of research on the risk level of work posture at PT Intiprama Global Service when carrying out goods transport activities manually, the results of the calculations were that 5 informants had a very high risk level, and based on the results of the Nordic Body Map (NBM) calculations, 2 informants had complaints about the musculoskeletal system. with a very high level, 2 informants with a high level, and 1 informant with a medium level.